Activation of phospholipase D by alpha-thrombin or epidermal growth factor contributes to the formation of phosphatidic acid, but not to observed increases in 1,2-diacylglycerol. - Wright, T M (1992)
The receptor-mediated activation of a phosphatidylcholine-hydrolysing phospholipase D (PLD) has recently been described. We investigated the effect of alpha-thrombin and epidermal growth factor (EGF) on cellular PLD activity in order to determine the role of this enzyme in mitogen-induced increases in phosphatidic acid and sn-1,2-diacylglycerol. In the presence of ethanol, stimulation of [3H]myristic acid-labelled quiescent IIC9 cells with alpha-thrombin or EGF resulted in a rapid increase in radiolabelled phosphatidyl-ethanol which reached a plateau at 1 min, indicating the rapid and transient activation of PLD. We observed a concomitant decrease in the mitogen-stimulated increase of radiolabelled phosphatidic acid. In contrast, ethanol did not significantly effect the elevation of sn-1,2-diacylglycerol levels stimulated by alpha-thrombin or EGF as determined by measurement of sn-1,2-diacylglycerol mass or the appearance of [3H]1,2-diacylglycerol. A novel lipid, detected by two-dimensional t.l.c. analysis, was generated in [3H]myristic acid-labelled cells stimulated with alpha-thrombin, but not EGF, in the presence of ethanol. Treatment in vitro of cellular lipids isolated from [3H]myristic acid-labelled cultures with PLD in the presence of ethanol also resulted in the generation of this novel lipid species, supporting the role of this enzyme in its production. These data indicate that in quiescent IIC9 cells: (a) alpha-thrombin or EGF rapidly and transiently activates a PLD; (b) although this activation is responsible for part of the mitogen-induced increases in phosphatidic acid, it does not contribute to induced increases in sn-1,2-diacylglycerol; and (c) activation of this enzyme appears to be involved in the formation of a novel lipid generated in response to alpha-thrombin, but not EGF, in IIC9 fibroblasts.